Water column raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M180 - Maren Walter; Mia Schumacher (PANGAEA, 2024)
Water column bathymetry data were collected aboard RV Meteor during cruise M180 using a Kongsberg EM122 multibeam echosounder. The expedition took place during 23.02.2022 - 14.04.2022 from Montevideo (Uruguay) - Cape Town (South Africa) in the Central and Southern Atlantic Ocean. The main aim of M180 is to better understand the fluxes and dissipation of oceanic and atmospheric energy cycles in the surface layer and the ocean interior to improve the parameterisation of these processes in climate models. Data were recorded outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. The main aim of M180 is to better understand the fluxes and dissipation of oceanic and atmospheric energy cycles in the surface layer and the ocean interior to improve the parameterisation of these processes in climate models. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.